Pharmacoepidemiological Tracing of patients admitted to the Emergency Room of a Hospital in the interior of Minas Gerais (Research, Society and Development, 2021)
This study aims to measure and present epidemiological data that can contribute to the management of a hospital in the interior of Minas Gerais, in order to improve the quality of services offered. This is a retrospective, cross-sectional observational study with a qualitative-quantitative approach. The hospital is small, containing 46 beds.  The sampling technique used is non-probability for convenience only. The MS Excel tool, version 2007, was used for data collection and analysis. The information was extracted using the following variables: Age, gender, reason for admission, medications used, and outcomes. The sample analyzed contains 9.246 admission forms for the emergency room. Among the samples, 1.328 were included (14.36%) and 7.918 were excluded (85.64%). The female gender is the majority in the sample space, (61.39%), while the male gender represents (38.60%). The most frequent ages are between 0 to 10 years (19.14%), 11 to 20 years (12.88%), and 41 to 50 years (15.06%). The most common complaints are:  Upper Respiratory tract infections (URTIs) had a total relative mean of 15.64%; lumbago 10.35%; asthmatic crisis 5.69%. The most used drugs are: Dipyrone, total relative mean of 17.33%; Dexamethasone 12.06%; Diclofenac 8.74%. The total relative average release rate is 95.80% while the total relative average hospitalizations are 4.20%. It is concluded that, knowing the pharmacoepidemiological outline of a hospital environment is to be able to provide the entire staff of employees with the profile of patients admitted, as well as being the basis for the identification and analysis of the real needs by the managers. However, it is necessary to emphasize that the study in question opens paths for the construction of future works, aimed at understanding the frequency of return of them to the emergency room referring to the same complaints, as well as the percentage of patients released, with drug therapy prescribed for later acquisition on an outpatient basis.